2019
DOI: 10.1371/journal.pone.0217759
|View full text |Cite
|
Sign up to set email alerts
|

Hostile attribution bias and angry rumination: A longitudinal study of undergraduate students

Abstract: Angry rumination and hostile attribution bias are important cognitive factors of aggression. Although prior theoretical models of aggression suggest that aggressive cognitive factors may influence each other, there are no studies examining the longitudinal relationship between angry rumination and hostile attribution bias. The present study used cross-lagged structural equation modeling to explore the longitudinal mutual relationship between hostile attribution bias and angry rumination; 941 undergraduate stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 30 publications
(46 reference statements)
3
13
0
2
Order By: Relevance
“…The items were answered on a 4‐point scale, ranging from 1 (almost never) to 4 (almost always). In line with previous studies using this scale, items were averaged to extract a global anger rumination score (Wang et al, 2019). Higher scores correspond to a higher level of anger rumination.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The items were answered on a 4‐point scale, ranging from 1 (almost never) to 4 (almost always). In line with previous studies using this scale, items were averaged to extract a global anger rumination score (Wang et al, 2019). Higher scores correspond to a higher level of anger rumination.…”
Section: Methodsmentioning
confidence: 99%
“…On the empirical level, many studies have shown that anger rumination predicts higher levels of aggression (Quan et al, 2020; Salguero et al, 2020; Wang et al, 2019), but the opposite association, whether involvement in aggressive behavior predicts an increase in anger rumination, has not been analyzed. Moreover, with regard to cyberaggression specifically, as far as we know only one study—with a cross‐sectional design and using middle adolescents—has found an association with anger rumination (Yang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The Chinese versions of the scale have been found to have adequate reliability and validity in prior studies (Maxwell, 2007;Luo & Liu, 2017;Wang, Cao, Dong, & Xia, 2019). In the present study, the confirmatory factor analysis (CFA) showed that the two factors model fit with the data well, χ 2 = 2.93, df = 2, root mean square error of approximation (RMSEA) = 0.03, comparative fit index (CFI) = 0.99, Tucker-Lewis Index (TLI) = 0.99, and standardized root mean square residual (SRMR) = 0.01.…”
Section: Angry Ruminationmentioning
confidence: 98%
“…Second, hostile attribution bias is always accompanied by aggressive emotions (Dodge et al, 2015), and aggressive emotions facilitate the generation of DAB (Denson et al, 2006). Finally, hostile attribution bias has predicted anger rumination in longitudinal research (Wang et al, 2019), which is an important element of DAB (Denson et al, 2006). In summary, hostile attribution bias may provide an emotional and cognitive basis for generating DAB.…”
Section: Interpersonal Openness and Dabmentioning
confidence: 99%